SIKAP GURU TERHADAP PENDIDIKAN MULTIKULTURAL DI SMP N 34 KERINCI - Tri Nurzarahmawati (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
v>This article will explain and describe the attitudes of teachers towards multicultural education in SMP N 34Kerinci. This study uses a qualitative approach with the type of descriptive research. The technique forselecting informants is purposive sampling. A number of informants is 10 people. Data collected throughinterviews, observation and documentation. Interviews conducted are in-depth interview techniques andobservations conducted are non-participation observation techniques. Data were analyzed using theinteractive analysis technique of Miles and Huberman (Interactive analysis model) consisting of datareduction, data models and conclusion drawing. The results revealed that teachers already have a positiveattitude towards multicultural education. Each teacher has the same attitude significantly seeing thedifferences in gender and language in the school. An understanding of multicultural education is animportant step to foster teacher attitudes and positive values. Citizenship subject teachers are found to havemore positive attitudes when compared to other subject teachers, which already have values contained inmulticultural education such as democratic values, humanism values and pluralism. Based on the findings itcan be suggested that more research should be needed on how to develop, change teaching methods andprograms in accordance with multicultural education and why certain subject teachers have a more positiveattitude towards multicultural education and increase the participation of teachers in cultural exch